The importance of a waste policy in the agroindustry of the Açaí do Amazonas (Euterpe precatoria Mart.) (Research, Society and Development, 2022)
Although Law 12,305 of 2010, which regulates the National Policy on Solid Waste, in its Art.3, item V, establishes the selective collection and collection of solid waste according to its chemical constitution, as well as the norms established by the Bodies of the National System of Environment (Sisnama); National Health Surveillance System (SNVS); Unified Agricultural Health Care System (Suasa); National Metrology, Standardization and Industrial Quality System (Sinmetro), the açaí agroindustry in the state of Amazonas has progressively intensified and one of the worrying factors today is the inadequate disposal of biomass from the processing of this industry, and the lack of awareness of the correct disposal of these wastes, as an environmental risk factor even in the face of clear evidence of climate change occurring on the planet. One of the Sustainable Development Goals (SDG 12) emphasizes issues related to sustainable consumption and production and in this context the United Nations (UN) recommends, by the year 2030, the reduction by half of food waste in production chains. and supply, including post-harvest losses. This article addresses some parameters related to the metrics of governance and management of açaí agro-industrial residues in the state of Amazonas, pointing out conceptual models of alternatives used in various inputs within the norms adopted by national and international public policies.